FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN ODHA DALAM MENJALANI TERAPI ANTIRETROVIRAL (ARV) - Rondonuwu, Rolly Harvie Stevan; Karlina, Nonok; Fitriana, Nur Gilang; Kartadarma, Supriyatni; Askur, Askur (Ensiklopedia of Journal, 2024)
ARV treatment adherence is necessary for successful treatment. Non-adherence in treatment can lead to failure of low virology first-line treatment regimens. This study aims to determine the factors associated with adherence of PLWHA in undergoing Antiretroviral (ARV) therapy at the VCT Clinic of Selasih Hospital, Pelalawan Regency. The study was quantitative in nature with a cross sectional approach. The population was all PLWHA who received ARV therapy as many as 116 people. The sample size of 54 respondents was taken using accidental sampling technique. Measuring instrument research questionnaire. Data analysis with chi square test. The results showed that the majority of high knowledge 41 respondents (75.9%) negative motivation as many as 34 respondents (63%), family did not support as many as 28 respondents (51.9%), There is a relationship between motivation (p=0.006) and family support (p=0.014) with PLWHA compliance in undergoing ARV therapy. It is concluded that the variables associated with adherence of PLWHA in undergoing ARV therapy are motivation and family support. It is recommended to respondents to be able to increase motivation and compliance in undergoing Antiretroviral (ARV) therapy by picking up drugs on time to the hospital and taking ARV drugs in a disciplined manner.Keywords: Antiretrovirals, Motivation, PLHIV, Knowledge